Health Policies, Health Politics : The British and American Experience, 1911-1965 - Fox, Daniel M. (Book collections on Project MUSE., 2014)
Drawing on a wide range of sources, from popular literature, movies, and television drama to government and institutional documents, this book reveals similarities in the presumptions underlying British and American health policies, while also exploring the distinctive way in which policy was shaped by political culture, class relationships, and economic resources in each country. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Pri.